A Theory-Based Measure of the Output of the Education Sector - Astrid Oline Ervik; Erling Holmøy; Torbjørn Hægeland (Statistics Norway, Research Department, 2003)
The paper estimates the output of the Norwegian higher education sector based on a modification of the methodology introduced by Jorgenson and Fraumeni (JF) (1989). JF measure output in the education sector by the increase in the total discounted lifetime income that can be attributed to the education "produced" in a given year. As opposed to JF, our output measure excludes the value of non-market labour activities. We provide a theoretical rationale for this modification of the JF-methodology, which has a great negative impact on the output estimates. Our baseline estimate of value added in the Norwegian higher education sector is still more than 8 times higher than the corresponding figure in the Norwegian National Accounts (NA). Replacing the standard NA figures by our estimate raises the share of higher education in GDP from 1.0 to 7.3 percent.
Keywords: H11; H52; I21; J24; 330; Human capital formation; Measurement of the education sector